Implementasi Multi Akad (Hybrid Contract) pada Pembiayaan Murabahah Bank Syariah - Ono, Inyoman Budi (Mu’amalah: Jurnal Hukum Ekonomi Syariah, 2023)
This study aims to explore the types of transactions in Islamic banks that utilize Multi Akad (Hybrid Contracts) within the framework of Islamic Economic Law (fiqh mu'amalah). Hybrid Contracts, or Multi Contracts, are combinations of several contracts in a single transaction (mujtami') or multiple reciprocal contracts (mutaqabil). These contracts represent an Ijtihad (juridical effort) designed to support the products of Islamic banks and other Islamic financial institutions, enabling them to conduct transactions in compliance with Islamic law. A qualitative descriptive method was employed in this research, with data collected from leaders and employees of Islamic bank branches in Parepare, Makassar, and Jakarta via mobile communication. Secondary data was gathered through literature review. The findings indicate that the use of Multi Akad (Hybrid Contracts) is most prevalent in Islamic bank murabaha financing transactions. In these transactions, the Murabahah contract is typically combined with a wakalah contract, resulting in a Murabahah bil Wakalah (Hybrid Contract).